Enhanced adsorption removal of methyl orange from aqueous solution by nanostructured proton-containing δ-MnO21. Issue 10 (14th March 2015) - Liu, Yan; Luo, Chao; Sun, Jian; Li, Haizhen; Sun, Zebin; Yan, Shiqiang
<x xml:space="preserve">Abstract</x> Two nanostructured proton-containing δ-MnO2 (H-δ-MnO2) materials were synthesized through proton exchange for K-containing δ-MnO2 (K-δ-MnO2) nanosheets and nanoparticles prepared by the hydrothermal homogeneous precipitation method and solid-state reaction.